2019
DOI: 10.1016/j.trci.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dementia in the US population using Medicare claims: Insights from linked survey and administrative claims data

Abstract: Introduction Medicare claims data may be a rich data source for tracking population dementia rates. Insufficient understanding of completeness of diagnosis, and for whom, limits their use. Methods We analyzed agreement in prevalent and incident dementia based on cognitive assessment from the Health and Retirement Study for persons with linked Medicare claims from 2000 to 2008 (N = 10,450 persons). Multinomial logistic regression identified sociodemographic factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(135 citation statements)
references
References 50 publications
3
118
1
Order By: Relevance
“…These results are generally consistent with recent, related work, which also found overall and race-specific differences in who is identified as having dementia when using ADAMS, L.-K.-W., and Medicare claims to identify persons with dementia [25,26]. However, here we took a more comprehensive approach, considering 9 different classification strategies and also considering how the use of different algorithms impacts risk factor associations.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…These results are generally consistent with recent, related work, which also found overall and race-specific differences in who is identified as having dementia when using ADAMS, L.-K.-W., and Medicare claims to identify persons with dementia [25,26]. However, here we took a more comprehensive approach, considering 9 different classification strategies and also considering how the use of different algorithms impacts risk factor associations.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…Depending on the data source, there can be vastly different prevalence and incidence estimates. For instance, the Health and Retirement Study linked to Medicare administrative claims data has shown that cognitive test results from survey data vs diagnoses from claims data can yield different incidence for dementia . For example, among whites, incidence of dementia based on cognitive tests from surveys was lower than that using diagnosis codes from claims (3.2% vs 12.3%) .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Health and Retirement Study linked to Medicare administrative claims data has shown that cognitive test results from survey data vs diagnoses from claims data can yield different incidence for dementia . For example, among whites, incidence of dementia based on cognitive tests from surveys was lower than that using diagnosis codes from claims (3.2% vs 12.3%) . In contrast, among blacks, dementia incidence was higher using cognitive tests compared to that using diagnosis codes (15.2% vs 11.1%) …”
Section: Discussionmentioning
confidence: 99%
“…Much of our understanding about the characteristics of people with AD/ADRD diagnoses who are receiving health care is based on data from Medicare fee‐for‐service and nationally representative surveys. These studies estimate the prevalence of diagnosed AD/ADRD in the United States to be 7% to 14% 6‐11 . Yet, one‐third of Medicare beneficiaries are enrolled in MA plans 12 .…”
Section: Introductionmentioning
confidence: 99%